A 100 W-level ultra-narrow fiber-coupled 780 nm diode laser - Longfei Jiang; Rui Wang; Huizi Zhao; Jianyong Sun; Qingshan Liu; Zining Yang; Hongyan Wang; Weiqiang Yang; Weihong Hua; Xiaojun Xu (High Power Laser Science and Engineering, 2024)
We report a high-power ultra-narrow fiber-coupled diode laser using a Faraday anomalous dispersion optical filter (FADOF) as an external cavity element. An external cavity suitable for both the fiber-coupled package and FADOF configuration has been proposed. Using a 87Rb-based FADOF as the frequency-selective element, we realized a 103 W continuous laser output with a uniform circular beam. The center wavelength was precisely locked at the D2 line of the Rb resonance, and the bandwidth was narrowed from 1.8 nm (free-running, full width at half maximum (FWHM)) to 0.013 nm (6.9 GHz, FWHM). The side mode suppression ratio reached 31 dB. Such diode lasers with precise wavelength and high spectral brightness have critical applications in many fields, such as high-energy gas laser pumping, spin-exchange optical pumping, Raman spectroscopy and nonlinear optics.